The influence of hydrated lime, Portland cement and cement dust on rheological properties of recycled cold mixes with foamed bitumen - Buczyński, Przemysław; Iwański, Marek (International Conference “Environmental Engineering”, 2017)
This article presents a laboratory evaluation of the viscoelastic properties of recycled base courses produced with different fillers. The aim of this study was to investigate the influence of loading time and temperature on the complex modulus (E*) and the phase angle (φ) of recycled base courses with respect to selected additives used. The mixtures contained reclaimed asphalt pavement RAP, crushed stone from existing base courses and virgin aggregate. Foamed bitumen 50/70 at 2.5% was used as a binder. The hydraulic binder constituted 3.0% of the recycled base course mixture. Portland cement, hydrated lime and cement kiln dust CKD were added as fillers. Evaluation of rheological properties of recycled base courses according to selected additives was carried out to the procedure set out in EN 1269726 annex D. The evaluation of stiffness modulus was conducted in the direct tension-compression test on cylindrical samples (DTC Y ). The samples were subjected to the cycles of sinusoidal strain with an amplitude εo < 25 . All tests were performed over a range of temperatures (5 ºC, 13 ºC, 25 ºC, 40 ºC) and loading times (0.1 Hz, 0.3 Hz, 1 Hz, 3 Hz, 10 Hz, 20 Hz). The results were used to model stiffness modulus master curves of the recycled base courses containing selected additives in the hydraulic binder.